2003
DOI: 10.1016/j.addr.2003.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Collagens—structure, function, and biosynthesis

Abstract: The extracellular matrix represents a complex alloy of variable members of diverse protein families defining structural integrity and various physiological functions. The most abundant family is the collagens with more than 20 different collagen types identified so far. Collagens are centrally involved in the formation of fibrillar and microfibrillar networks of the extracellular matrix, basement membranes as well as other structures of the extracellular matrix. This review focuses on the distribution and func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

28
1,646
2
83

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 2,044 publications
(1,759 citation statements)
references
References 104 publications
28
1,646
2
83
Order By: Relevance
“…4) and could be a reflection of the need for a stiff matrix that could give support and protection to the blastema cells during locomotion in a terrestrial environment. In general, collagen fibers are one of the most abundant proteins of the extracellular matrix, which confers cell protection against mechanical forces (Gelse, Pöschl, & Aigner, 2003). We suggest that the presence of this mature collagen fiber underlying the wound epidermis in B. ramosi could be a protection mechanism for blastema cells during locomotion.…”
Section: Discussionmentioning
confidence: 99%
“…4) and could be a reflection of the need for a stiff matrix that could give support and protection to the blastema cells during locomotion in a terrestrial environment. In general, collagen fibers are one of the most abundant proteins of the extracellular matrix, which confers cell protection against mechanical forces (Gelse, Pöschl, & Aigner, 2003). We suggest that the presence of this mature collagen fiber underlying the wound epidermis in B. ramosi could be a protection mechanism for blastema cells during locomotion.…”
Section: Discussionmentioning
confidence: 99%
“…We have shown, rather, that Scx is required for middle ear tendon differentiation, though the underlying molecular mechanism remains elusive. In forelimb tendons of Scxnull embryos, collagen XIV (Gelse et al 2003) and tenomodulin (Brandau et al 2001) expression are lost, and collagen I levels are decreased . Moreover, direct regulation of collagen I enhancers has been demonstrated (Lejard et al 2007;Espira et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The reticulum of dense ECM elements observed within the plaques is structurally similar to that reported by Nakamura et al (46) in aging rats and differs from the normal basal lamina found in nondiseased arteries. Type IV collagen is typically located within the endothelial basal lamina in healthy blood vessel walls (47). The presence of type IV collagen in the dense ECM subtending the endothelium suggests that the observed thickened reticulum subtending the plaque endothelial cells is a modified form of the endothelial basal lamina.…”
Section: Discussionmentioning
confidence: 99%